Use of Spearman's rank correlation in Least Angle Regression (Bangladesh Journal of Scientific Research, 2011)
Key words: Least Angle Regression; Linear regression; Product-moment correlation; Spearman's rank correlationBangladesh J. Sci. Res. 23(2): 129-136, 2010 (December)